2019
DOI: 10.1021/acsaelm.9b00229
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conductive Printable Meshes Based on Percolation Patterns

Abstract: Transparent conductive meshes were fabricated by inkjet printing on flexible substrate using a percolation pattern created by random removal of conducting bonds from a regular square two-dimensional lattice. With this approach, a higher gain in optical transmittance than electrical conductivity loss is achieved above the percolation threshold. As a result of this, a figure of merit for the percolation pattern is improved with respect to a regular square mesh. The transmittance (T), sheet resistance (R), and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Such foils are flexible to bending but withstand distortion under stress. We studied pristine PET foil as delivered (Melinex ST505, 125 μm thick) with different amounts of oxygen plasma cleaning as well as PET foils spin-coated with PS, PMMA, and PEDOT:PSS in our lab to vary the surface energy of ink and substrate. , Finally, we tested a commercial foil with a 20 μm-thick layer of mesoporous silica (JS-220 Novele from NovaCentrix), which had shown superb printing behavior in an earlier study …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such foils are flexible to bending but withstand distortion under stress. We studied pristine PET foil as delivered (Melinex ST505, 125 μm thick) with different amounts of oxygen plasma cleaning as well as PET foils spin-coated with PS, PMMA, and PEDOT:PSS in our lab to vary the surface energy of ink and substrate. , Finally, we tested a commercial foil with a 20 μm-thick layer of mesoporous silica (JS-220 Novele from NovaCentrix), which had shown superb printing behavior in an earlier study …”
Section: Methodsmentioning
confidence: 99%
“…26,27 Finally, we tested a commercial foil with a 20 μm-thick layer of mesoporous silica (JS-220 Novele from NovaCentrix), which had shown superb printing behavior in an earlier study. 2 We found that PET foils were somewhat curled as obtained, which caused problems for spin coating. Hence, we preheated the PET foils carefully before coating them to remove residual strain, with the exception of silica-coated PET foil, which was already flat.…”
Section: Substrate Preparationmentioning
confidence: 99%
See 2 more Smart Citations